1999
DOI: 10.1021/ja990404v
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergent Total Syntheses of (+)- and (−)-Scopadulcic Acid A

Abstract: The first enantioselective total synthesis of scopadulcic acid A is described. The key step is a cascade intramolecular Heck reaction of a methylenecycloheptene iodide, which generates the B, C, and D rings of the scopadulan ring system in 90% yield as a single stereoisomer. A distinctive feature of these syntheses is the use of stereoselective enolization to dictate which enantiomer of the natural product is produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(71 citation statements)
references
References 71 publications
1
67
0
3
Order By: Relevance
“…[29][30][31][32][33][34][35] Since Ishizaki and Hoshino 24 reported the first addition of alkynylzinc reagents to aldehydes in 1994, some chiral ligands, such as N-methylephedrine, 19 sulfonamide alcohol, 36 BINOL and its derivatives, [20][21][22][23] have successfully been applied to this reaction in recent years. The amino alcohol ligand shows excellent enantioselectivity for the alkynylzinc addition to aliphatic aldehydes, and the BINOL catalyst shows excellent enantioselectivity for the alkynylzinc addition to aromatic aldehydes.…”
Section: Scheme 1 Reported Bifunctional Binol Derivativesmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] Since Ishizaki and Hoshino 24 reported the first addition of alkynylzinc reagents to aldehydes in 1994, some chiral ligands, such as N-methylephedrine, 19 sulfonamide alcohol, 36 BINOL and its derivatives, [20][21][22][23] have successfully been applied to this reaction in recent years. The amino alcohol ligand shows excellent enantioselectivity for the alkynylzinc addition to aliphatic aldehydes, and the BINOL catalyst shows excellent enantioselectivity for the alkynylzinc addition to aromatic aldehydes.…”
Section: Scheme 1 Reported Bifunctional Binol Derivativesmentioning
confidence: 99%
“…The precursor of 144 was the corresponding chlorohydrin and lithium naphthalenide the lithiating reagent [86], meanwhile intermediates 145 [112], 146 [113] and 147 [114] were prepared by iodine±lithium exchange by means of t-BuLi. All of them reacted with electrophiles to yield polyfunctionalized compounds, compound 146 being used in the synthesis of scopadulcic acid A.…”
Section: C-functionalized Alkyllithium Compoundsmentioning
confidence: 99%
“…[2,3] Accordingly, much progress has been made in the asymmetric addition of terminal alkynes to aldehydes, which has been established as a reliable platform for the efficient synthesis of a wide array of chiral propargylic alcohols. [1,4] Various alkyne derivatives such as arylacetylene, alkylacetylene, ethynylcyclohexene, acetalacetylene, methyl propiolate, 1,3-diyne, and trimethylsilylacetylene have been used as the alkyne nucleophiles.…”
mentioning
confidence: 99%
“…Among the catalytic systems reported so far for the alkynylation of aldehydes, the amino-alcohol-Zn system is particularly noteworthy in terms of its operational simplicity and mild reaction conditions. The amino-alcohol-Zn catalytic system has attracted much attention since the pioneering contribution from Carreira and co-workers, who demonstrated that by using a combination of ZnA C H T U N G T R E N N U N G (OTf) 2 and Nmethylephedrine, the addition of terminal acetylenes to aldehydes afforded the desired products in high yields and enantioselectivities. [4b, 12] However, to the best of our knowledge, no impressive amino-alcohol-Zn system (except for Trosts dinuclear Zn catalyst) for the alkynylation of aldehydes with trimethylsilylacetylene has been reported so far, therefore a new, generally applicable procedure using amino-alcohol-Zn would still be highly desirable.…”
mentioning
confidence: 99%